ANALISIS PERAN GREEN ACCOUNTING, TATA KELOLA, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - MELLANI ANGELI; SURYANTO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to obtain empirical evidence on the influence of green accounting, tax planning, managerial ownership, audit committee, board size, dividend policy, profitability, and firm size on firm value. This research is expected to provide insight into additional factors that influence firm value. This study used a sample of all manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. A total of 46 manufacturing companies, equivalent to 138 data sets, met the research criteria. The sample was selected using a purposive sampling method and analyzed using multiple linear regression. The results show that managerial ownership and firm size have a positive influence on firm value. Management share ownership can increase investor confidence in the company, thereby increasing firm value. Larger companies have a higher level of stability. A company's stock price increases as a result of this stability in the capital market. Furthermore, green accounting, tax planning, audit committee, board size, dividend policy, and profitability have no effect on firm value.